Calvin’s Marks of the Church: A Call for Recovery - Eric J. Titus (Kairos (English Ed.))
As a reformer, Calvin struggled with the issue of the oneness of the church. If the church was no longer visibly one, two issues came to the fore. First, how and in what respect the churches of the Reformation could maintain the command of Christ to be one, and in what respect could one speak of a true visible church on earth. Calvin resolved the issues by tying the one, holy, and catholic church to the election of God on the one hand, and the true church in its earthly form to marks of the church on the other. The balance of this paper focuses upon these latter aspects, the marks which constitute the visible church of Christ on earth. This focus on the marks of the visible church is more than just a recounting of Calvin’s thought; it is also an invitation to recover their substance and to regain the essence of the church through this recovery.